EFFECT OF PROPHYLACTIC ANTIBIOTIC ON SURGICAL SITE INFECTION AFTER TENSION-FREE HERNIOPLASTY - Saskia-Javi, Y.; Sudartana, I K.; Raka-Widiana,; I G. (BALI MEDICAL JOURNAL, 2013)
Objective: prophylactic antibiotics were remains applied for hernioplasty treatment at Sanglah General Hospital Bali-Indonesia. On the other hand, there were no comprehensive infection incidence data gathered. This research aims to determine incidence differences of post operative infection in patients underwent tension-free hernioplasty and received prophylactic antibiotics compared to those who received placebo. The general purpose of this research is to determine the necessity of prophylactic antibiotics in the hope of setting new procedural standards in elective hernia procedures thus reducing cost and bacteria resistance. Patients and Method: This was an open label randomized clinical trial conducted at Sanglah General Hospital Department of General Surgery from October 2011. The target population was all patients who underwent tension-free hernioplasty procedure, in Sanglah General Hospital. The acquired data was analyzed after an independent t test was performed. a Mann-Whitney U test, Fisher’s exact test, and Two-Sample Kolmogorov-Smirnov test were used to determine the correlations between variables, where p < 0.05 was regardless of significant. Results: From 54 subjects 3 (5.6%) of them were found to have a slight erythema around the operation wound, on the 7th,14th,21th, and 28th day no signs of erythema were found. From the three subjects two (7.4%) were from the placebo group and one (3.7%) from the antibiotic group. All clinical assessment of post operative wound was made using Southampton Wound Assessment Scale, where erythema is a grade 1C, all subjects healed primarily. Conclusion: An Open Label Randomized Clinical Trial comparing SSI in post tension-free hernioplasty patients who were given prophylactic antibiotics and placebo. No significant difference were found.